The Investigation Process of Sexual Abuse Crimes Against Victims with Disabilities - Yosua Yulio Hoke; Hadi Tuasikal (JUSTISI, 2026)
This study aims to analyze the investigation process of sexual abuse crimes against persons with disabilities at the Sorong City Police Station and identify the factors that cause children with disabilities to be vulnerable to becoming victims. The research method used an empirical juridical approach with qualitative methods. Data were collected through in-depth interviews with investigators from the Sorong City Police Station's PPA Unit, analysis of legal documents such as the Criminal Procedure Code, Law No. 8/2016 on Persons with Disabilities, and Law No. 12/2022 on Sexual Violence Crimes, as well as field observations and literature studies. The novelty of this research lies in the development of an integrative investigation model based on trauma-informed care, specifically designed for the context of Sorong City, taking into account the unique characteristics of Eastern Indonesia. Unlike previous studies, which tended to be partial and theoretical, this study presents a holistic approach that integrates various important dimensions into a single operational framework that is ready for implementation. The results of the study show that the investigation process faces obstacles in the form of difficulties in communicating with victims with disabilities, limited evidence, and a lack of supporting facilities. Effective solutions include adaptive communication approaches and multisectoral collaboration. Factors contributing to the vulnerability of victims include the exploitation of their powerlessness by perpetrators,  the lack of inclusive sex education, social stigma, and the victims' dependence on perpetrators, who are often people close to them. These findings indicate the need for a specialized investigation approach and holistic prevention strategies. In conclusion, the investigation process for sexual abuse cases against persons with disabilities requires a specific approach that considers the needs of victims, including investigator training, adaptive communication protocols, and strengthening of supporting infrastructure. Prevention efforts should focus on eliminating vulnerability factors through strengthening inclusive sex education and public awareness campaigns.